Implementation of Youth Head Leader Strategies in Addressing Juvenile Delinquency in Yalahatan Hamlet, Amahai District, Central Maluku Regency - Anike Jacomina. M. Manuputty; Johan Tanamal (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
This study aims to analyze the implementation of youth leaders' strategies in addressing juvenile delinquency in Yalahatan Hamlet, Amahai District, Central Maluku Regency. Juvenile delinquency is a social problem that can hinder the development of the younger generation, thus requiring the active involvement of various parties, including youth organizations. This study used qualitative methods with data collection techniques through interviews, observation, and documentation. Research informants consisted of youth leaders, parents, community/religious leaders, and local youth. The results showed that the strategies implemented included a persuasive approach, coaching through weekly sports activities, monthly religious activities, community service, and mentoring and supervision of youth. The implementation of these strategies showed changes in the behavior of some youth towards a more positive direction, such as increased participation in community activities and reduced deviant behavior. In addition, the youth leaders collaborated with the village government and community/religious leaders in implementing the coaching program. This strategy contributed to increasing youth involvement in positive activities, strengthening community social control, and reducing juvenile delinquency in the Yalahatan Hamlet environment. However, its implementation still faces obstacles in the form of low participation of some youth and limited supporting facilities. Therefore, ongoing synergy between youth organizations, the community, and the government is needed to create a conducive environment for youth development and guidance.